Impact Analysis of Economic Factors, Education, and Access to Resources on Income Gap in Yogyakarta - Sufri Mashuri; Nasruddin Nasruddin; Loso Judijanto; Maman Hariana (West Science Social and Humanities Studies, 2023)
This research delves into the intricate dynamics of income inequality in Yogyakarta, focusing on the interplay of Access to Resources, Economic Factors, Education, and the resulting Income Gap. Utilizing a quantitative approach, the study employs Structural Equation Modeling to analyze data collected from a diverse sample. The findings reveal significant relationships between these socio-economic variables, shedding light on the nuanced factors contributing to income disparities. Access to Resources emerges as a pivotal factor, alongside the influence of Economic Factors and the mitigating effect of Education. The results carry profound policy implications, emphasizing the need for targeted interventions to enhance resource accessibility, foster inclusive economic development, and promote educational opportunities. This research contributes to the broader discourse on income inequality, offering actionable insights for policymakers, researchers, and practitioners invested in creating a more equitable socio-economic landscape in Yogyakarta.